DAYA TARIK BAHASA ALAY DALAM KOMUNIKASI DI KALANGAN REMAJA PENGGUNA BLACBERRY MESSENGER WONOKROMO, SURABAYA - Anbertu, Elysabeth; Darmawan, Arif; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2016)
This alay language is not only a communication tool, but also an identification tool. Teenagers usingthis alay language may be to identify themselves as alay. The use of alay language can also be useful tocultivate self-existence. One language application as a communication tool is the use of language inelectronic media applications Blacberry Messenger (BBM). The purpose of the study to determine thephenomenon of alay language attraction in communication among adolescents on the use of fuel in thedistrict Wonokromo Surabaya. drag rational alay language as communication among adolescents to the useof fuel in sub-district Wonokromo Surabaya, alay language users, alay language can provide other benefits,as a means of non-formal communication among teenagers alay and other teenagers alay language alsoprovide benefits, especially for their community especially. The emotional appeal of the alay language as acommunication among teenagers in the use of fuel in Surabaya, the motivation of adolescents to use alaylanguage in BBM is essentially to search for self-identity, self-existence according to cultural developmentand recognition of the outside world of their existence (alayers) in adolescents today. Many activities can bedone using alay language, among others, SMS, chat with fellow alay community on Facebook, yahoomessenger, or just write a wall or coment on Facebook either with fellow users alay or with other BBMusers. The attractiveness of the alay language is diverse ranging from alay language writing that looksunique that can be modified or mixed with the letters, besides that alay language can also be a codelanguage for them (alayers) in communicating within their community in particular.Keywords: Alay Language, Communication, BBM